Neuromuscular fatigue and mechanical alterations in intermittent activities: applications to racket sports - Girard, O. (Medicine and Science in Tennis, 2007)
On December 1st 2006, Olivier Girard presented his Ph.D. thesis titled `Neuromuscular fatigue and mechanical alterations in intermittent activities: applications to racket sports`, concluding five intensive years (including a master`s degree on the same topic) of study on the analysis of racket sport determinants at the Faculty of Sports Science in Montpellier in the South of France.